(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
An investigation was carried out from January 2021 to December 2022 to study the lichen flora of Khadimnagar National Park. The present paper deals with 10 new records of lichens, namely, Acanthothecis asprocarpa (A.W. Archer) A.W. Archer, Bacidia absistens (Nyl.) Arnold, Caloplaca cinnabarina (Ach.) Zahlbr., Coenogonium implexum Nyl., Dirinaria leopoldii (Stein) D. D. Awasthi, Echinoplaca campanulata Kalb & Vězda, Metamelanea umbonata Henssen, Pyrgillus javanicus (Mont. & Bosch) Nyl., Ramboldia blastidiata Kantvilas & Elix and Trypethelium ochroleucum (Eschw.) Nyl. Detailed taxonomic description of the newly reported species with photographs are provided. Bangladesh J. Plant Taxon. 30(2): 175-183, 2023 (December)